1992
DOI: 10.1002/cne.903170304
|View full text |Cite
|
Sign up to set email alerts
|

Secondary vestibular cholinergic projection to the cerebellum of rabbit and rat as revealed by choline acetyltransferase immunohistochemistry, retrograde and orthograde tracers

Abstract: Previously we have shown that four regions of the cerebellum, the uvula-nodulus, flocculus, ventral paraflocculus, and anterior lobe 1, receive extensive, but not exclusive, cholinergic mossy fiber projections. In the present experiment we have studied the origin of three of these projections in the rat and rabbit (uvula-nodulus, flocculus, ventral paraflocculus), using choline acetyltransferase (ChAT) immunohistochemistry in combination with a double label, retrogradely transported horseradish peroxidase (HRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 56 publications
5
61
1
Order By: Relevance
“…The CVN have functions in addition to autonomic regulation, as this region projects to the cerebellar nodulus and uvula (Epema et al 1985;Sato et al 1989;Thunnissen et al 1989;Barmack et al 1992) as well as to the dorsal horn of the upper cervical spinal cord (Peterson et al 1978;Bankoul et al 1995). The present data indicate that these areas mainly receive from the CVN relatively simple signals regarding head position or head velocity, at least during rotations in vertical planes.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The CVN have functions in addition to autonomic regulation, as this region projects to the cerebellar nodulus and uvula (Epema et al 1985;Sato et al 1989;Thunnissen et al 1989;Barmack et al 1992) as well as to the dorsal horn of the upper cervical spinal cord (Peterson et al 1978;Bankoul et al 1995). The present data indicate that these areas mainly receive from the CVN relatively simple signals regarding head position or head velocity, at least during rotations in vertical planes.…”
Section: Discussionsupporting
confidence: 49%
“…For example, a specialized projection to the upper cervical spinal cord arises from the CVN (Peterson et al 1978); this projection differs from the classical vestibulospinal tracts in that it terminates mainly in the dorsal horn (Bankoul et al 1995), and is presumably involved in modulating the processing of sensory signals from neck receptors. The CVN also provide considerable inputs to the cerebellar nodulus and uvula (Epema et al 1985;Sato et al 1989;Thunnissen et al 1989;Barmack et al 1992). Furthermore, the CVN project to medullary regions that participate in regulation of blood pressure and breathing (Balaban and Beryozkin 1994;Yates et al 1995;Ruggiero et al 1996;Porter and Balaban 1997;Martinelli et al 2007), and lesions of the CVN abolish cardiovascular and respiratory responses to stimulation of vestibular afferents (Uchino et al 1970;Yates et al 1993;Kerman and Yates 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we also demonstrated that axons expressing choline acetyl-transferase (ChAT) are found in heterotopia using immunocytochemistry [5]. In the present report GFP-labeled axons were present in heterotopia after injection into the NPP which is known to contain ChAT-expressing neurons with cerebellar projections [27]. These data confirm the presence of cholinergic axons in heterotopia and now reveal the source of these afferent which include the NPP.…”
Section: Discussionsupporting
confidence: 87%
“…Barmack described many ChAT-immunoreactive cells dorsally in the VNC of the rabbit (Barmack et al 1992b(Barmack et al , 1992c. The location of these cells appears to overlap the calretinin area, raising the possibility that some of the calretinin-immunoreactive cells might be cholinergic.…”
Section: Calretininmentioning
confidence: 99%